Night-time immobilization of the distal interphalangeal joint reduces pain and extension deformity in hand osteoarthritis - Watt, F; Kennedy, D; Carlisle, K; Freidin, A; Szydlo, R; Honeyfield, L; Satchithananda, K; Vincent, T (Oxford University Press, 2014)
Objective. DIP joint OA is common but has few cost-effective, evidence-based interventions. Pain and deformity [radial or ulnar deviation of the joint or loss of full extension (extension lag)] frequently lead to functional and cosmetic issues. We investigated whether splinting the DIP joint would improve pain, function and deformity. Methods. A prospective, radiologist-blinded, non-randomized, internally controlled trial of custom splinting of the DIP joint was carried out. Twenty-six subjects with painful, deforming DIP joint hand OA gave written, informed consent. One intervention joint and one control joint were nominated. A custom gutter splint was worn nightly for 3 months on the intervention joint, with clinical and radiological assessment at baseline, 3 and 6 months. Differences in the change were compared by the Wilcoxon signed rank test. Results. The median average pain at baseline was similar in the intervention (6/10) and control joints (5/10). Average pain (primary outcome measure) and worst pain in the intervention joint were significantly lower at 3 months compared with baseline (P = 0.002, P = 0.02). Differences between intervention and control joint average pain reached significance at 6 months (P = 0.049). Extension lag deformity was significantly improved in intervention joints at 3 months and in splinted joints compared with matched contralateral joints (P = 0.016). Conclusions. Short-term night-time DIP joint splinting is a safe, simple treatment modality that reduces DIP joint pain and improves extension of the digit, and does not appear to give rise to non-compliance, increased stiffness or joint restriction.